2015
DOI: 10.1534/g3.114.014555
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofMTAPInhibits Tumor-Related Phenotypes in HT1080 Cells via a Mechanism Unrelated to Its Enzymatic Function

Abstract: Methylthioadenosine Phosphorylase (MTAP) is a tumor suppressor gene that is frequently deleted in human cancers and encodes an enzyme responsible for the catabolism of the polyamine byproduct 5′deoxy-5′-methylthioadenosine (MTA). To elucidate the mechanism by which MTAP inhibits tumor formation, we have reintroduced MTAP into MTAP-deleted HT1080 fibrosarcoma cells. Expression of MTAP resulted in a variety of phenotypes, including decreased colony formation in soft-agar, decreased migration, decreased in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…However, Dou et al [ 23 ] observed an inverse correlation between cellular differentiation and MTAP relative expression in colorectal cancer, mainly due to promoter demethylation in more malignant tumors. Tang et al [ 24 ] demonstrated that the tumor suppressor function of MTAP in HT1080 fibrosarcoma cells is not the same as its known enzymatic function.…”
Section: Discussionmentioning
confidence: 99%
“…However, Dou et al [ 23 ] observed an inverse correlation between cellular differentiation and MTAP relative expression in colorectal cancer, mainly due to promoter demethylation in more malignant tumors. Tang et al [ 24 ] demonstrated that the tumor suppressor function of MTAP in HT1080 fibrosarcoma cells is not the same as its known enzymatic function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the apparent selection pressure for subclones with loss of MTAP in skin and retention of MTAP in the peripheral blood of patients with SS is intriguing and remains to be explained but could reflect a role for the skin microenvironment that is not present in the peripheral blood. Interestingly, a recent study suggested that MTAP may act as a tumor suppressor independently of its enzymatic function (Tang et al, 2014); however, the precise mechanism remains unclear. Analysis using additional Q-PCR probes demonstrated 75% and 58.3% concordance for MTAP and CDKN2A, respectively, between probe sets 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is expressed virtually in all tissues throughout the body, and its homozygous deletion is frequently associated with solid and hematologic tumors such as mesothelioma, lung carcinoma, hepatocellular carcinoma, gastrointestinal stromal tumors, metastatic melanoma, leukemias, and lymphoma [18,[21][22][23][24][25]. Therefore, MTAP has been reported as a tumor suppressor gene [24,[26][27][28][29][30]; however, many studies have demonstrated the contradictory function of MTAP. For instance, the loss of MTAP expression has been associated with inhibition of growth and progression of head and neck carcinoma and lung cancer by MTA accumulation [31,32].…”
Section: Introductionmentioning
confidence: 99%